Peran tenaga kesehatan dalam menanggulangi bencana alam demi kesejahteraan masyarakat - Husnani, Daulah (Maliki Interdisciplinary Journal, 2024)
Indonesia is a country with a high risk of natural disasters. Natural disasters are disasters caused by events or a series of events caused by nature, including earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides. Disasters are divided into several phases, namely Pre-Disaster, Impact, Emergency, and Reconstruction. The role of health workers in disaster management is very important, because the role of health workers is to devote themselves in the health sector for the welfare of the community.